2014
DOI: 10.1007/s00244-014-0013-y
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical Production of Atmospheric Carbonyls in a Rural Area in Southern China

Abstract: For the first time, ambient carbonyls were measured in a rural area in southern China from August 2012 to February 2013 to investigate their distribution characteristics and sources. Formaldehyde, acetaldehyde, and acetone were the three most abundant carbonyls, which accounted for 83-95 % of total seven carbonyls identified. The O3 formation potential of carbonyls in summer (59.55 μg/m(3)) was approximately ten times greater than that (6.37 μg/m(3)) in winter, and calculated photolysis rates were significantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 53 publications
1
7
0
Order By: Relevance
“…The formaldehyde and acetaldehyde concentrations in the present study were lower than those reported in downtown Monterrey, Nuevo Leon, Mexico by Menchaca-Torre et al [42] and similar to those reported in Chendu (China) [49], but higher than those reported in Longmen Southern China during 2012-2013 by Guo et al [50].…”
Section: Results For C 1 -C 2 Carbonylssupporting
confidence: 79%
“…The formaldehyde and acetaldehyde concentrations in the present study were lower than those reported in downtown Monterrey, Nuevo Leon, Mexico by Menchaca-Torre et al [42] and similar to those reported in Chendu (China) [49], but higher than those reported in Longmen Southern China during 2012-2013 by Guo et al [50].…”
Section: Results For C 1 -C 2 Carbonylssupporting
confidence: 79%
“…It was also higher than coastal cities such as Qinzhou and Yantai [22,23] of China. The concentration of acetone in Jinan is higher than that in rural and forest areas [24], especially in the similar mountainous area of Guiyang [25]. Compared with mega cities affected by photochemical smog processes, such as Beijing, Shanghai and Guangzhou [26][27][28], the concentration levels of formaldehyde and acetaldehyde in Jinan were much lower.…”
Section: Concentrations Of Atmospheric Carbonylsmentioning
confidence: 99%
“…In addition to odor, the carbonyl compounds have also attracted the attention of researchers to measure their concentrations in ambient air because of their ozone formation potential by means of photochemical reactions and their adverse health effects on humans [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%